Rational assembly of functional Co-MOFs via a mixed-ligand strategy: synthesis, structure, topological variation, photodegradation properties and dye adsorption. Issue 34 (9th August 2018) - Fan, Chuanbin; Zong, Ziao; Zhang, Xia; Xu, Cungang; Zhu, Zheng; Meng, Xiangmin; Bi, Shuangyu; Fan, Yuhua
Abstract : Four novel Co(ii ) metal–organic frameworks were synthesized employing a rational design approach under solvothermal conditions. Abstract : Four novel Co(ii ) metal–organic frameworks, namely [Co2 (4, 4′-cpmb)2 (1, 1′-bbi)2 ] n (1 ), [Co(4, 4′-cpmb)(4, 4′-bbibp)] n (2 ), [Co(4, 4′-cpmb)(tib)]·3(H2 O) n (3 ) and [Co(4, 4′-sdc)(tib)]·(H2 O) n (4 ) (flexible 4, 4′-cpmb = 4-(4-carboxylphenylmethylthio)benzoic acid, rigid 4, 4′-sdc = 4, 4′-stilbenedicarboxylic acid, flexible 1, 1′-bbi = 1, 1′-(1, 4-butanediyl)bis(imidazole), rigid 4, 4′-bbibp = 4, 4′-bis(benzoimidazo-1-ly)biphenyl and rigid tib = 1, 3, 5-tris(1-imidazolyl)benzene) were synthesized employing a rational design approach under solvothermal conditions and further characterized by elemental analysis, IR spectra, thermogravimetric (TG) analysis, powder X-ray diffraction (PXRD), and single-crystal X-ray diffraction. The four Co-MOFs display different interpenetrated structures due to the flexibility of O/N-donor ligands. Single-crystal X-ray diffraction analysis reveals that complex1 displays a 6-fold interpenetrating classIa net with the point Schläfli symbol of (6 6 ). Complex2 shows a 3-fold interpenetratingsqc5 net with the point Schläfli symbol of (6 6 ·8). Complexes3 and4 exhibit a 2-fold interpenetrating 4-connectedsql topology with the point Schläfli symbol of (4 4 ·6 2 ). The photodegradation properties and dye adsorption capacity of complexes1–4 are investigated, and the framework integrity of complexes1–4 can be well-retained.